What Drives Firms to Enter Carbon Market? An Experimental Evidence - Wijayanti, Dwi Marlina (The International Journal of Financial Systems, 2024)
Carbon exchange is a very new issue in Indonesia. Therefore, understanding the potential of carbon exchange to realize Net-Zero Emission is crucial. This study explores the factors that can encourage companies to enter the carbon exchange by understanding behavioral and non-behavioral factors. Psychological theory is also used to explain the motivation of corporate managers in making strategic decisions. This study is a quantitative study using experiments. The experimental design used is 2x2x2 between subjects. Data were analyzed using analysis of variance (ANOVA). The results of this study indicate that regulatory pressure, financial incentives, and international trade are factors that can encourage companies to enter the carbon exchange/carbon market. In addition, carbon trading is unable to outperform carbon taxes in the short term due to cost efficiency and investment costs in companies. In addition, this study can be a reference for policy makers to optimize the role of IDXCarbon in carrying out its functions and encourage more companies to be involved in carbon exchange trading to realize Net-Zero Emission by 2060.